STIMULATION OF INVESTMENT PROCESSES IN THE ECONOMY OF UKRAINE IN ORDER TO INCREASE ITS COMPETITIVENESS - CHEREP, OLEKSNDR; CHEHOVSKAYA, LERA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
An urgent problem facing Ukraine is the justification of the need to stimulate investment processes to increase its competitiveness and gain a strong position in the international market. After all, ensuring the competitiveness of the economy is a priority of any state that cares about its place in the world market and its economic growth. The level of investment significantly depends on the economic attractiveness of Ukrainian enterprises, as competitive enterprises are an important factor in the success of investors. The formation of the country’s investment attractiveness is necessary to ensure its competitiveness, solve social problems. Effective use of foreign direct investment in the national economy can be an important factor in accelerating economic growth, optimizing the reproductive structure of the economy, solving many other strategic tasks. Accumulated foreign investment is one of the indicators that reflects the level of integration of the country into the world economy, the development of its foreign economic relations and the desire to create an open, export-oriented model of the economy. Ukraine lags far behind most countries with economies in transition in this regard. The paper presents the results of research by leading organizations on the investment attractiveness of Ukraine in 2020. It is established that increasing the country’s competitiveness entails an increase in investment. It is determined that the need for sustainable economic growth, which contributes to increased productivity, remains critical to improving living standards. Ways to improve the investment climate in Ukraine are proposed. The results of the work are a system of proposals to improve investment activity.